Small-holder farmers knowledge and information on the impact of climate variability & extremes on livestock production in Limpopo & Mpumalanga Provinces - Nesamvuni, Azwihangwisi E.; Ndwambi, Khuthadzo; Tshikolomo, Khathutshelo A.; Lekalakala, Gabriel R.; Raphulu, Thomas; Petja, Brilliant M.; Van Niekerk, Johan (Technium Social Sciences Journal, 2022)
A study was carried out to investigate the level of awareness, knowledge and information of small-holder farmers (SHLF) on the impact of climatic change (CC) and extremes on livestock production in Limpopo and Mpumalanga Provinces. At least 366 smallholder farmers were interviewed using a semi-structured questionnaire to elicit responses on vulnerability. Almost all the farmers (96 %) have heard about CC only a few farmers (4 %) did not know CC. The medium for the conveyance of CC information was the main radio (94.32%). Newspapers and television were also efficient mediums in the conveyance of this information, each with the outreach of 16.76 and 32.67%, respectively. Central to the impact of CC was the fact that (90%) of the farmers confirmed that there was a change in grass availability; which contributed to major livestock fatalities of which over half of the farmers (55.19%) attested as the cause. The study found that 86.67% of SHLF who attended awareness meetings indicated that the discussions prioritized adapting to CC. However, SHLF (80.77%) did not have an early warning system. This was coupled with a lack of contingency plans by (84.36%) the farmers to deal with the impact of the said drought on their farms. SHLF (19%) who had facilitated contingency plans indicated that improved aspects of the plan should incorporate the support of their provision feeds, drilling of boreholes, and erection of dams. Based on SHLF perceptions there is a need for strategic shifts from grazing to small scale feed-lots.